Preparation method of high-purity vanadium-aluminum alloy with low nitrogen content and low impurity content

By using vacuum environment and argon gas charging and pressure-recharge in the aluminum thermal smelting furnace, combined with the technology of circulating water cooling in the furnace shell, the problems of high nitrogen content and high impurities in the preparation of vanadium aluminum alloy in the prior art were solved, and the preparation of low nitrogen and low impurities of high-purity vanadium aluminum alloys was achieved, and Al2O3 in the furnace ash was used for the preparation of ceramic materials.

CN119640036APending Publication Date: 2025-03-18HEBEI GAOYE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510034693.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to safely and efficiently prepare high-purity vanadium aluminum alloys with low nitrogen content and low impurities, and it is easy to cause splash during the reaction and lead to V loss. The use of CaO slag-making agent will introduce impurities.

Method used

By using a vacuum environment and argon pressure in the aluminum thermal smelting furnace, the contact between oxygen and nitrogen in the air and reactants is reduced, and the loss of reaction heat and the introduction of impurities are avoided. At the same time, circulating water is used to cool the furnace shell to condense the Al2O3 component in the smoke, which is used to prepare ceramic materials and avoid the use of CaO slag-making agent.

Benefits of technology

The preparation of high-purity vanadium aluminum alloy with low nitrogen content and low impurities was achieved, avoiding the loss of reaction heat and the introduction of impurities, improving the purity and smelting efficiency of the alloy, and using Al2O3 in the furnace ash for the preparation of ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640036A_ABST
    Figure CN119640036A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metallurgy, and discloses a preparation method of a low-nitrogen-content and low-impurity high-purity vanadium-aluminum alloy, which comprises the following steps: step 1, controlling the purity, granularity and content of raw materials; 2, baking the raw materials and mixing the raw materials; step 3, charging; step 4, smelting; step 5, coarse crushing; sixthly, sand blasting treatment is conducted; and step 7, crushing, refining, screening, detecting and packaging. According to the method, the content of the added aluminum oxide cooling material is controlled, the vacuum environment is applied to the smelting process, argon is introduced until the pressure in the furnace is-0.08 MPa after vacuumizing is stopped, volatilization of elements in the alloy is reduced, and the beneficial effect that the loss of reaction heat and the influence of impurities such as oxygen and nitrogen in air on the purity of the alloy are avoided is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a method for preparing a high-purity vanadium-aluminum alloy with low nitrogen content and low impurities. Background Art

[0002] Vanadium aluminum alloy is the main raw material for preparing alloys containing vanadium and aluminum and pure vanadium. Since the melting point and density of vanadium and aluminum are very different, most of the vanadium aluminum (V-Al) alloys are prepared by aluminothermic reduction at home and abroad. YS / T 579-2014 stipulates the chemical composition of four grades of alloys, AlV55, AlV65, AlV75 and AlV85, to meet the raw material requirements for the production of V-Al alloys, such as the preparation of Ti6Al4V and pure V. Vanadium oxides include V2O3, VO2, V2O5, etc., and the heat release of V2O5 is the largest. Therefore, the aluminothermic reduction method generally uses V2O5 powder and Al powder as raw materials. However, it is also because the heat release of the reduction reaction is very large when using V2O5 raw materials. Therefore, the aluminothermic reaction is self-propagating, releases heat violently, has a fast reaction speed and a short time (10s to 3min, generally less than 90s), and the reaction process is difficult to control, but the calming time is long (6 to 96h) [see CN113957274A]. Therefore, splashing is easily caused during the reaction, resulting in the loss of V. CN117604354A discloses the use of V2O5 with a particle size of 80±10 mesh as a raw material, and the return slag of ferrovanadium with a mass ratio of 10 to 15% of V2O5 is added as a coolant. Although the reaction is controlled, the repeated use of the coolant also easily leads to a high content of Fe and Si in the prepared AlV85 alloy. CN117604256A and CN117144170A disclose the use of graphite crucibles to add CaO or lime in aluminothermic reaction, which, on the one hand, acts as a coolant to reduce the intensity of the reaction, and on the other hand, reduces the melting point of the slag, improves the fluidity of the slag, and promotes the separation of slag and gold. However, the CaO or lime used contains more impurities. CN113957274A discloses that the furnace body of the smelting furnace is a graphite crucible, the inner wall of the graphite crucible is coated with fused magnesium fire mud, and the standing time after the reaction is 72 to 96 hours. However, the service life of the furnace lining made of graphite material is relatively short, and the recycling of the furnace lining cannot be achieved, which seriously restricts the increase in alloy output and the reduction in production costs. At the same time, the use of furnace linings not only increases the complexity of the process but also pollutes the vanadium aluminum alloy. Moreover, most of the patents such as CN113957274A, CN117144170A, and CN117604256A adopt ignition outside the furnace and react and prepare in an open reactor. Although the equipment is simple and easy to operate, the open reaction causes serious heat loss, and slag-forming agents such as CaO have to be added to reduce the melting point of the slag to ensure the fluidity of the slag; at the same time, the open reaction causes oxygen (O) and nitrogen (N) in the air to participate in the reaction, resulting in excessive contents of O, N and carbon (C) in the product, and causing mismatch in the aluminum content of the reaction; and it is very difficult to purify N, C and Si in the V-Al alloy using subsequent vacuum melting and vacuum electron beam melting technology; the open reaction also causes a large amount of generated smoke to spread in the production environment, causing a series of problems such as environmental protection and operator safety.Therefore, there is currently a lack of corresponding preparation technology at home and abroad on how to safely and efficiently prepare high-purity vanadium-aluminum alloys with low nitrogen content and low impurities. Summary of the invention

[0003] Technical issues solved:

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a high-purity vanadium-aluminum alloy with low nitrogen content and low impurities, which has the advantages of avoiding the loss of reaction heat and the influence of impurities such as oxygen and nitrogen in the air on the purity of the alloy. Circulating water is introduced into the furnace shell for cooling, which accelerates the condensation of smoke generated in the furnace body to the surface of the inner shell of the furnace body to collect the new product of furnace ash with the main component of Al2O3, which is used for the preparation of ceramic materials, does not require the use of CaO slag-forming agent, and avoids the introduction of impurities, thereby solving the problems existing in the above-mentioned technology.

[0005] Technical solution:

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities, comprising the following steps:

[0007] Step 1: Control the purity, particle size and content of raw materials: Based on the quality of V2O5 powder, configure V2O5 powder, Al powder and Al2O3 coolant according to the rated composition of V-Al alloy grade specified in YS / T579-2014 standard;

[0008] Step 2, baking raw materials and mixing: Put the V2O5 powder into a stainless steel plate, and then put it into a drying oven at 100-130°C for 2-6 hours to remove the moisture therein; then mix the dried V2O5 powder, the newly opened packaged Al powder, and the Al2O3 cooling material into a dry powder mixer, mix for 2-5 hours, and let it stand to obtain a mixture;

[0009] Step 3, furnace loading: install the cleaned reactor consisting of the lower annular copper crucible and the upper annular cast iron crucible into the aluminothermic smelting furnace in sequence, spread the mixture obtained in the second step into the reactor layer by layer in 3 to 5 layers, and use a flat hammer with an end diameter of not less than 100 mm to compact and flatten it, then spread 10 to 25 g of magnesium chips ignition agent on the top of the mixture, spread the magnesium chips into a circle with a diameter of 100 to 300 mm, finally insert the heating wire of the ignition wire into the ignition agent, check the sealing rings of all interfaces, cover the furnace cover with cooling circulating water and lock it, and complete the furnace loading;

[0010] Step 4, smelting: evacuate the aluminothermic smelting furnace to a vacuum degree of less than 10Pa, then stop evacuating and fill with argon until the pressure in the furnace is -0.08MPa, press the ignition button, ignite the ignition agent to start the self-propagating reaction smelting of the alloy, and start evacuating the furnace body after 30 to 60 minutes, observe the temperature change in the furnace, and stop evacuating after the alloy is left to stand until the temperature in the smelting furnace is lower than 100°C, and complete the smelting of the alloy;

[0011] Step 5, coarse crushing: open the furnace cover, collect the ash on the furnace wall, and obtain the ash product; disassemble the crucible connection of the reactor, separate the obtained alloy cake from the slag, manually finish and use a grinder to remove the slag and defects on the surface of the alloy cake, and coarsely crush it into blocks of 50 to 100 mm to complete the coarse crushing;

[0012] Step 6: Sandblasting: Place the roughly crushed block into a shot blasting machine for 5 to 10 minutes to remove the oxide film on the surface of the block alloy. Use quartz sand with a particle size of 0.5 to 1 mm and a sandblasting pressure of 0.5 to 0.8 MPa to complete the sandblasting.

[0013] Step 7: Crushing, refining, screening, testing and packaging: Put the shot peened blocks into the crusher for crushing and screening to 0.25-6.30 mm or select the required sieve size according to user needs, take samples of the sieved alloy for chemical composition analysis, and package and store after qualified analysis to complete the preparation of the alloy;

[0014] The grades of the V-Al alloy include: AlV55-AlV85.

[0015] Preferably, in the AlV55 alloy, the mass of Al powder is 0.868 to 1.055 times the mass of V2O5 powder, and the mass of Al2O3 coolant is 0.21 to 0.61 times the mass of V2O5 powder.

[0016] Preferably, in the AlV65 alloy, the mass of Al powder is 0.735 to 0.867 times the mass of V2O5 powder, and the mass of Al2O3 coolant is 0.20 to 0.59 times the mass of V2O5 powder.

[0017] Preferably, in the AlV75 alloy, the mass of Al powder is 0.635 to 0.734 times the mass of V2O5 powder, and the mass of Al2O3 coolant is 0.19 to 0.58 times the mass of V2O5 powder.

[0018] Preferably, in the AlV85 alloy, the mass of Al powder is 0.557 to 0.634 times the mass of V2O5 powder, and the mass of Al2O3 coolant is 0.16 to 0.55 times the mass of V2O5 powder.

[0019] Preferably, the purity of the V2O5 powder is not less than 99.0%, and Fe≤0.01%, Si≤0.03%, C≤0.01%, N≤0.1%, and the particle size is greater than 325 mesh≤0.045mm.

[0020] Preferably, the Al powder has a purity of not less than 99.9%, Fe≤0.015%, O≤0.071%, C≤0.02%, N≤0.01%, and a particle size of ≤0.075 mm through 200 mesh.

[0021] Preferably, the Al2O3 coolant uses Al2O3 powder or returned slag with a particle size of 1 to 3 mm, and the purity of the Al2O3 powder is required to be not less than 99.0%, wherein Fe≤0.05%, Si≤0.02%, N≤0.02%, and C≤0.01%.

[0022] Preferably, the purity of the Al2O3 returned slag is not less than 99.0%, and the impurity elements contained therein are Fe≤0.05%, Si≤0.03%, N≤0.08%, and C≤0.05%.

[0023] The essence of the reaction of reducing V2O5 with Al, 3V2O5+10Al=6V+5Al2O3, is carried out step by step through four reactions: 3V2O5+2Al=6VO2+Al2O3, 6VO2+2Al=3V2O3+Al2O3, 3V2O3+2Al=6VO+Al2O3, 6VO+4Al=6V+2Al2O3, where the melting temperature of V2O5 is 670-678℃, and the starting temperature of the first reaction is also 670~678℃; the melting temperatures of VO2, V2O3 and VO are 1363℃, 1957℃ and 1700℃ respectively. The adiabatic combustion temperature of the thermite reaction is 2748℃, and the unit heat effect is 4538~4988kJ / kg.

[0024] The melting temperature of Al2O3 is 2054~2072℃, and the heat required to melt into liquid is 3665kJ / kg. Therefore, the unit heat effect produced by the thermite reaction completely melts Al2O3; further, at the adiabatic temperature of thermite reaction (2748℃), the melting heat of Al2O3 is 4621kJ / kg, which is basically equivalent to the unit heat effect produced by thermite reaction. Therefore, the intensity of thermite reaction can be controlled by the Al2O3 content without introducing new impurities. Moreover, when the temperature is lower than 2054℃, the heat absorption of Al2O3 is low, and when it reaches 2054℃, the heat absorption increases by 651kJ / kg, thereby controlling the degree and progress of the reaction.

[0025] The aluminothermic reaction process proceeds normally, and the heat generated by each gram of charge in the reaction only needs to be no less than 2511-2302 kJ / kg. Therefore, there will be an excess of 2027-2686 kJ / kg of heat that needs to be controlled; adding 22-49% of the mass of the V2O5 raw material Al2O3 can absorb this part of the heat by melting Al2O3, thereby effectively controlling the degree of reaction, reducing the intensity of the reaction, and effectively avoiding liquid splashing and V volatilization loss; considering the purity of V2O5, the different content of added aluminum and to ensure the full progress of the reaction, 16-63% of the mass of the V2O5 raw material Al2O3 is added.

[0026] The melting point of Al2O3 is 2054℃ and the boiling point is 2980℃. Therefore, the amount of Al2O3 added during the reaction is small, and the Al2O3 generated by the thermite reaction is mainly volatilized in the form of smoke. In an open reactor, these fumes are directly volatilized into the production environment. After the furnace body is sealed and the furnace shell is cooled with circulating water, these high-temperature fumes are condensed and deposited on the inner wall of the furnace to form furnace ash, which is used as Al2O3 powder in other industrial production.

[0027] Compared with the prior art, the present invention provides a method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities, which has the following beneficial effects:

[0028] 1. The present invention applies a vacuum environment to the smelting process, evacuates the aluminum hot smelting furnace to a vacuum degree less than 10Pa, and in the vacuum state, oxygen and nitrogen in the air are excluded, greatly reducing their contact with the reactants, thereby avoiding the formation of impurities between oxygen and nitrogen and the alloy during the reaction, and filling argon gas to a furnace pressure of -0.08MPa. The purpose of filling argon gas is to obtain a certain pressure and reduce the volatilization of elements in the alloy (equivalent to increasing the vapor pressure in the furnace, and a higher content of argon gas can maintain a higher pressure in the furnace to avoid the volatilization of vanadium and aluminum in the alloy during the smelting process); at the same time, the magnesium ribbon cannot be ignited under vacuum conditions, and a little oxygen is required, so the vacuum is not evacuated to a very low level at the beginning; after the reaction is completed, it is necessary to evacuate the furnace again, and this time it is to reduce oxidation and the formation of impurities, thereby achieving the beneficial effect of avoiding the loss of reaction heat and the influence of impurities such as oxygen and nitrogen in the air on the purity of the alloy.

[0029] 2. The present invention reduces the temperature of the inner surface of the furnace body by introducing cooling water into the furnace shell, thereby making it easier for the gas and smoke volatiles generated during the high-temperature smelting process to condense into solid particles. By controlling the cooling temperature of the furnace shell, it is ensured that the useful component Al2O3 in the smoke quickly condenses into tiny particles after contacting the cooling surface, reducing the volatilization loss of the substance and improving the collection efficiency. Since the aluminum oxide component in the reaction gas is mainly cooled and solidified, the collected ash component is mainly Al2O3. The Al2O3 extracted from the ash has good thermal stability and mechanical properties, and is very suitable for the manufacture of ceramic materials. Its physical properties also make it show excellent wear resistance in ceramic products, achieving the beneficial effect of introducing circulating water cooling into the furnace shell, accelerating the condensation of the smoke generated in the furnace body to the surface of the furnace shell to collect the new ash product with the main component of Al2O3 for the preparation of ceramic materials.

[0030] 3. The present invention does not use CaO, thereby making the alloy composition more stable during the smelting process, reducing the composition fluctuation caused by the reaction of the slag-forming agent with the main reactant, and reducing the temperature required for the overall smelting by not using CaO, thereby saving energy and reducing the smelting cost, achieving the beneficial effect of not needing to use a CaO slag-forming agent and avoiding the introduction of impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the overall preparation steps of the present invention; DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] Preparation of AlV85 alloy

[0035] The first step is to control the purity, particle size and content of raw materials

[0036] Weigh 100 kg of V2O5 powder, 55.7 kg of Al powder and 16 kg of Al2O3 powder (equivalent to a mass ratio of V2O5:Al:Al2O3=1:0.557:0.16) respectively, and place them in stainless steel pans for use.

[0037] The purity of V2O5 powder is 99.9%, and the impurities it contains are 0.0053% Fe, 0.0227% Si, 0.0073% C, 0.0815% N, and the particle size exceeds 325 mesh (≤0.045mm); the purity of Al powder is 99.9%, and the impurities it contains are 0.015% Fe, 0.0710% O, 0.0170% C, 0.0031% N, and the particle size passes 200 mesh (≤0.075mm); the particle size of Al2O3 powder is 1-3mm, the purity is 99.9%, and the impurity elements it contains are 0.038% Fe, 0.0187% Si, 0.0086% C, and 0.0142% N.

[0038] Step 2: Baking raw materials and mixing

[0039] Put the V2O5 powder into a stainless steel plate, and then put it into a DHG-4 electric constant temperature blast drying oven at 100°C for 6 hours to remove the moisture therein; then mix the dried V2O5 powder, the newly opened packaged Al powder, and the Al2O3 cooling material into a W-type double cone mixer for 5 hours, and let it stand to obtain a mixture;

[0040] Step 3: Install the furnace

[0041] The reactor consisting of the annular copper crucible on the lower layer and the annular cast iron crucible on the upper layer which have been cleaned up is sequentially installed in the aluminothermic smelting furnace, the mixed material obtained in the second step is layered into the reactor in 3 layers, and a flat hammer with an end face diameter of 100 mm is used to compact and flatten it, and then 10 g of magnesium chips ignition agent is spread on the top of the mixed material, and the magnesium chips are spread into a circle with a diameter of 100 mm, and finally the heating furnace wire of the ignition wire is inserted into the ignition agent, the sealing rings of all interfaces are checked, and the furnace cover through which the cooling circulating water is passed is covered and locked, and the furnace loading is completed;

[0042] Step 4: Smelting

[0043] The aluminum hot smelting furnace is evacuated to a vacuum degree of less than 10Pa, and then the evacuation is stopped and argon is filled to a pressure of -0.08MPa in the furnace. The ignition button is pressed to ignite the ignition agent to start the self-propagating reaction smelting of the alloy. After 30 minutes, the furnace body is evacuated to observe the temperature change in the furnace. After the alloy is left to stand until the temperature in the smelting furnace is lower than 100°C, the evacuation is stopped to complete the smelting of the alloy.

[0044] Step 5: Coarse crushing

[0045] The furnace cover was opened, and the ash on the furnace wall was collected to obtain 36.5 kg of ash product; the crucible connection of the reactor was disassembled, and the obtained alloy cake was separated from the slag to obtain 102 kg of Al2O3 return slag, and the slag and defects on the surface of the alloy cake were removed by manual finishing and a grinder, and the cake was roughly crushed into blocks of 50 to 100 mm to complete the rough crushing;

[0046] Among them, the alloy cake still has a small amount of attached slag and defects after being separated from the slag;

[0047] Step 6: Sandblasting

[0048] The roughly crushed block was placed in a shot blasting machine for 10 minutes to remove the oxide film on the surface of the block alloy. Quartz sand with a particle size of 1 mm was selected and the blasting pressure was 0.8 MPa to complete the blasting process.

[0049] Step 7: Crushing, sieving, testing and packaging

[0050] The shot peened blocks are placed in a crusher for crushing and screening to 0.25 mm. The screened alloy samples are sampled for chemical composition analysis. After passing the analysis, they are packaged and stored to complete the preparation of the alloy.

[0051] The AlV85 alloy prepared in this embodiment was subjected to chemical composition analysis. As shown in Table 1, the mass percentages of V and Al were 87.5884% and 12.0827%, respectively, wherein the mass percentages of O, N and C were 0.1456%, 0.0022% and 0.0172%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0052] Example 2

[0053] Preparation of AlV85 alloy

[0054] The first step is to control the purity, particle size and content of raw materials

[0055] Weigh 200kg of V2O5 powder and 119kg of Al powder (equivalent to mass ratio: V2O5:Al=1:0.595) respectively, and put them in stainless steel plates for use. The purity and particle size of V2O5 powder and Al powder are the same as the first step of Example 1. The Al2O3 coolant uses the Al2O3 return slag smelted with Al2O3 powder in Example 1, which is crushed into 1-3mm. The purity is better than 99.0% (99.8%), and the impurity elements contained therein are 0.047% Fe, 0.0276% Si, 0.0317% N, and 0.0384% C. Weigh 80kg of Al2O3 return slag powder (equivalent to mass ratio: V2O5:Al2O3=1:0.4);

[0056] Step 2: Baking raw materials and mixing

[0057] Put the V2O5 powder into a stainless steel plate, and then put it into a DHG-4 electric constant temperature air drying oven at 130°C for 2 hours to remove the moisture therein; then mix the dried V2O5 powder, the newly opened packaged Al powder, and the Al2O3 cooling material into a W-type double cone mixer for 2 hours, and let it stand to obtain a mixture;

[0058] Step 3: Install the furnace

[0059] The reactor consisting of the annular copper crucible on the lower layer and the annular cast iron crucible on the upper layer which have been cleaned is sequentially installed in the aluminothermic smelting furnace, the mixed material obtained in the second step is layered into the reactor in 4 layers, and compacted and flattened using a flat hammer with an end face diameter of 150 mm, and then 18 g of magnesium chips ignition agent is spread on the top of the mixed material, and the magnesium chips are spread into a circle with a diameter of 200 mm, and finally the heating furnace wire of the ignition wire is inserted into the ignition agent, the sealing rings of all interfaces are checked, and the furnace cover through which the cooling circulating water is passed is covered and locked, and the furnace loading is completed;

[0060] Step 4: Smelting

[0061] The aluminothermic smelting furnace is evacuated to a vacuum degree less than 10Pa, then the evacuation is stopped and argon gas is filled to a pressure of -0.08MPa in the furnace. The ignition button is pressed to ignite the ignition agent to start the self-propagating reaction smelting of the alloy. After 50 minutes, the furnace body is evacuated to observe the temperature change in the furnace. After the alloy is left to stand until the temperature in the smelting furnace is lower than 100°C, the evacuation is stopped to complete the smelting of the alloy.

[0062] Step 5: Coarse crushing

[0063] The implementation steps are the same as the fifth step of Example 1; 112 kg of ash product and 228 kg of Al2O3 return slag are obtained;

[0064] Step 6: Sandblasting

[0065] The coarsely crushed block was placed in a shot blasting machine for 5 minutes to remove the oxide film on the surface of the block alloy. Quartz sand with a particle size of 0.5 mm and a blasting pressure of 0.8 MPa were used to complete the blasting process.

[0066] Step 7: Crushing, sieving, testing and packaging

[0067] The shot peened blocks are placed in a crusher for crushing and screening to 6.30 mm. The screened alloy samples are taken for chemical composition analysis. After the analysis is qualified, they are packaged and stored to complete the preparation of the alloy.

[0068] The AlV85 alloy prepared in this embodiment was subjected to chemical composition analysis. As shown in Table 1, the mass percentages of V and Al were 84.6789% and 15.0230%, respectively, wherein the mass percentages of O, N and C were 0.1234%, 0.0024% and 0.0121%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0069] Example 3

[0070] Preparation of AlV85 alloy

[0071] The first step is to control the purity, particle size and content of raw materials

[0072] 300 kg of V2O5 powder, 190.2 kg of Al powder and 165 kg of Al2O3 powder were weighed respectively (equivalent to a mass ratio of V2O5:Al:Al2O3=1:0.634:0.55), and placed in stainless steel pans for later use; the purity and particle size of the three raw materials were the same as the first step of Example 1;

[0073] Step 2: Baking raw materials and mixing

[0074] Put the V2O5 powder into a stainless steel plate, and then put it into a blast drying oven at 120°C for 4 hours to remove the moisture therein; then mix the dried V2O5 powder, the newly opened Al powder and the Al2O3 powder into a double cone mixer for 4 hours, and let it stand to obtain a mixture;

[0075] Step 3: Install the furnace

[0076] The reactor consisting of the annular copper crucible on the lower layer and the annular cast iron crucible on the upper layer which have been cleaned up is sequentially installed in the aluminothermic smelting furnace, the mixed material obtained in the second step is layered into the reactor in 5 layers, and a flat hammer with an end face diameter of 150 mm is used to compact and flatten it, and then 25 g of magnesium chips ignition agent is spread on the top of the mixed material, and the magnesium chips are spread into a circle with a diameter of 300 mm, and finally the heating furnace wire of the ignition wire is inserted into the ignition agent, the sealing rings of all interfaces are checked, and the furnace cover through which the cooling circulating water is passed is covered and locked, and the furnace loading is completed;

[0077] Step 4: Smelting

[0078] The aluminothermic smelting furnace is evacuated to a vacuum degree of less than 10Pa, and then the evacuation is stopped and argon gas is filled to a pressure of -0.08MPa in the furnace. The ignition button is pressed to ignite the ignition agent to start the self-propagating reaction smelting of the alloy. After 60 minutes, the furnace body is evacuated to observe the temperature change in the furnace. After the alloy is left to stand until the temperature in the smelting furnace is lower than 100°C, the evacuation is stopped to complete the smelting of the alloy.

[0079] Step 5: Coarse crushing

[0080] The implementation steps are the same as the fifth step of Example 1; 195 kg of furnace ash product and 314 kg of Al2O3 return slag are obtained;

[0081] Step 6: Sandblasting

[0082] The coarsely crushed block was placed in a shot blasting machine for 8 minutes to remove the oxide film on the surface of the block alloy. Quartz sand with a particle size of 0.8 mm and a blasting pressure of 0.8 MPa were used to complete the blasting process.

[0083] Step 7: Crushing, sieving, testing and packaging

[0084] The shot peened blocks are placed in a crusher for crushing and screening to 3.0 mm. The screened alloy samples are taken for chemical composition analysis. After the analysis is qualified, they are packaged and stored to complete the preparation of the alloy.

[0085] The AlV85 alloy prepared in this embodiment was subjected to chemical composition analysis. As shown in Table 1, the mass percentages of V and Al were 82.2458% and 17.5190%, respectively, wherein the mass percentages of O, N and C were 0.1202%, 0.00207% and 0.0135%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0086] Example 4

[0087] Preparation of AlV75 alloy

[0088] The first step is to control the purity, particle size and content of raw materials

[0089] 100 kg of V2O5 powder, 63.5 kg of Al powder and 19 kg of Al2O3 powder were weighed respectively (equivalent to a mass ratio of V2O5:Al:Al2O3=1:0.635:0.19), and placed in stainless steel pans for later use; the purity and particle size of the V2O5 powder, Al powder and Al2O3 powder were the same as those in the first step of Example 1;

[0090] Step 2: Baking raw materials and mixing

[0091] Put the V2O5 powder into a stainless steel plate, and then put it into a constant temperature blast drying oven at 120°C for 5 hours to remove the moisture therein; then mix the dried V2O5 powder, the newly opened packaged Al powder, and the Al2O3 cooling material into a double cone mixer for 4 hours, and let it stand to obtain a mixture;

[0092] Step 3: Install the furnace

[0093] The reactor consisting of the annular copper crucible on the lower layer and the annular cast iron crucible on the upper layer which have been cleaned is sequentially installed in the aluminothermic smelting furnace, the mixed material obtained in the second step is layered into the reactor in 3 layers, and a flat hammer with an end diameter of 100 mm is used to compact and flatten it, and then 13 g of magnesium chips ignition agent is spread on the top of the mixed material, and the magnesium chips are spread into a circle with a diameter of 150 mm, and finally the heating furnace wire of the ignition wire is inserted into the ignition agent, the sealing rings of all interfaces are checked, and the furnace cover through which the cooling circulating water is passed is covered and locked, and the furnace loading is completed;

[0094] Step 4: Smelting

[0095] The aluminothermic smelting furnace is evacuated to a vacuum degree of less than 10Pa, and then the evacuation is stopped and argon gas is filled to a pressure of -0.08MPa in the furnace. The ignition button is pressed to ignite the ignition agent to start the self-propagating reaction smelting of the alloy. After 60 minutes, the furnace body is evacuated to observe the temperature change in the furnace. After the alloy is left to stand until the temperature in the smelting furnace is lower than 100°C, the evacuation is stopped to complete the smelting of the alloy.

[0096] Step 5: Coarse crushing

[0097] The furnace cover was opened, and the ash on the furnace wall was collected to obtain 27 kg of ash product; the crucible connection of the reactor was disassembled, and the obtained alloy cake was separated from the slag, and the slag and defects on the surface of the alloy cake were removed by manual finishing and a grinder, and the cake was roughly crushed into blocks of 50 to 100 mm to complete the rough crushing;

[0098] Step 6: Sandblasting

[0099] The roughly crushed block was placed in a shot blasting machine for 10 minutes to remove the oxide film on the surface of the block alloy. Quartz sand with a particle size of 1 mm was selected and the blasting pressure was 0.8 MPa to complete the blasting process.

[0100] Step 7: Crushing, sieving, testing and packaging

[0101] The shot peened blocks are placed in a crusher for crushing and screening to 2.0 mm. The screened alloy samples are analyzed for chemical composition. After passing the analysis, they are packaged and stored to complete the preparation of the alloy.

[0102] The AlV75 alloy prepared in this embodiment was subjected to chemical composition analysis. As shown in Table 1, the mass percentages of V and Al were 79.8877% and 19.8850%, respectively, wherein the mass percentages of O, N and C were 0.1182%, 0.0019% and 0.0131%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0103] Example 5

[0104] Preparation of AlV75 alloy

[0105] The first step is to control the purity, particle size and content of raw materials

[0106] 100 kg of V2O5 powder, 73.4 kg of Al powder and 58 kg of Al2O3 return slag (equivalent to mass ratio: V2O5:Al:Al2O3=1:0.734:0.580) were weighed respectively and placed in stainless steel pans for later use; the purity and particle size of the V2O5 powder, Al powder and Al2O3 return slag were the same as those in the first step of Example 2;

[0107] The second to seventh steps are the same as in Example 4;

[0108] In this embodiment, 99 kg of furnace ash was obtained; the chemical composition of the alloy AlV75 alloy prepared in this embodiment was analyzed. As shown in Table 1, the mass percentages of V and Al were 72.9010% and 26.8450%, respectively, and the mass percentages of O, N and C were 0.1251%, 0.0027% and 0.0212%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0109] Example 6

[0110] Preparation of AlV65 alloy

[0111] The first step is to control the purity, particle size and content of raw materials

[0112] 100 kg of V2O5 powder, 73.5 kg of Al powder and 20 kg of Al2O3 powder were weighed respectively (equivalent to a mass ratio of V2O5:Al:Al2O3=1:0.735:0.20), and placed in stainless steel pans for later use; the purity and particle size of the V2O5 powder, Al powder and Al2O3 return slag were the same as those in the first step of Example 1;

[0113] The second to seventh steps are the same as in Example 4;

[0114] In this embodiment, 42 kg of furnace ash was obtained; the chemical composition of the alloy AlV65 alloy prepared in this embodiment was analyzed. As shown in Table 1, the mass percentages of V and Al were 69.2757% and 30.4230%, respectively, and the mass percentages of O, N and C were 0.1234%, 0.0024% and 0.0153%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0115] Example 7

[0116] Preparation of AlV65 alloy

[0117] The first step is to control the purity, particle size and content of raw materials

[0118] 100 kg of V2O5 powder, 86.7 kg of Al powder and 59 kg of Al2O3 return slag (equivalent to mass ratio: V2O5:Al:Al2O3=1:0.867:0.590) were weighed respectively and placed in stainless steel pans for later use; the purity and particle size of the V2O5 powder, Al powder and Al2O3 return slag were the same as those in the first step of Example 2;

[0119] The second to seventh steps are the same as those in Example 4;

[0120] In this embodiment, 75 kg of furnace ash was obtained; the chemical composition of the alloy AlV65 alloy prepared in this embodiment was analyzed. As shown in Table 1, the mass percentages of V and Al were 61.6128% and 38.0827%, respectively, and the mass percentages of O, N and C were 0.1256%, 0.0022% and 0.0131%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0121] Example 8

[0122] Preparation of AlV55 alloy

[0123] The first step is to control the purity, particle size and content of raw materials

[0124] 100 kg of V2O5 powder, 86.8 kg of Al powder and 21 kg of Al2O3 powder were weighed respectively (equivalent to mass ratio: V2O5:Al:Al2O3=1:0.868:0.210), and placed in stainless steel pans for standby use; the purity and particle size of the V2O5 powder, Al powder and Al2O3 return slag were the same as those in the first step of Example 1;

[0125] The second to seventh steps are the same as those in Example 4;

[0126] In this embodiment, 41 kg of furnace ash was obtained; the chemical composition of the alloy AlV55 alloy prepared in this embodiment was analyzed. As shown in Table 1, the mass percentages of V and Al were 58.9395% and 40.7541%, respectively, and the mass percentages of O, N and C were 0.1099%, 0.0015% and 0.0143%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0127] Example 9

[0128] Preparation of AlV55 alloy

[0129] The first step is to control the purity, particle size and content of raw materials

[0130] 100 kg of V2O5 powder, 105.5 kg of Al powder and 61 kg of Al2O3 return slag (equivalent to mass ratio: V2O5:Al:Al2O3=1:1.055:0.610) were weighed respectively and placed in stainless steel pans for later use; the purity and particle size of the V2O5 powder, Al powder and Al2O3 return slag were the same as those in the first step of Example 2;

[0131] The second to seventh steps are the same as those in Example 4;

[0132] In this embodiment, 94 kg of furnace ash was obtained; the chemical composition of the alloy AlV55 alloy prepared in this embodiment was analyzed. As shown in Table 1, the mass percentages of V and Al were 51.9316% and 47.8038%, respectively, and the mass percentages of O, N and C were 0.1089%, 0.0013% and 0.0172%, respectively, which fully complies with the YS / T 579-2014 "Vanadium Aluminum Master Alloy" standard.

[0133] Table 1 Chemical composition of the alloy obtained in Example

[0134]

[0135] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities, characterized in that: The following steps are involved: Step 1: Control the purity, particle size and content of raw materials: Based on the quality of V2O5 powder, configure V2O5 powder, Al powder and Al2O3 coolant according to the rated composition of V-Al alloy grade specified in YS / T579-2014 standard; Step 2, baking raw materials and mixing: Put the V2O5 powder into a stainless steel plate, and then put it into a drying oven at 100-130°C for 2-6 hours to remove the moisture therein; then mix the dried V2O5 powder, the newly opened packaged Al powder, and the Al2O3 cooling material into a dry powder mixer, mix for 2-5 hours, and let it stand to obtain a mixture; Step 3, furnace loading: install the cleaned reactor consisting of the lower annular copper crucible and the upper annular cast iron crucible into the aluminothermic smelting furnace in sequence, spread the mixture obtained in the second step into the reactor layer by layer in 3 to 5 layers, and use a flat hammer with an end diameter of not less than 100 mm to compact and flatten it, then spread 10 to 25 g of magnesium chips ignition agent on the top of the mixture, spread the magnesium chips into a circle with a diameter of 100 to 300 mm, finally insert the heating wire of the ignition wire into the ignition agent, check the sealing rings of all interfaces, cover the furnace cover with cooling circulating water and lock it, and complete the furnace loading; Step 4, smelting: evacuate the aluminothermic smelting furnace to a vacuum degree of less than 10Pa, then stop evacuating and fill with argon until the pressure in the furnace is -0.08MPa, press the ignition button, ignite the ignition agent to start the self-propagating reaction smelting of the alloy, and start evacuating the furnace body after 30 to 60 minutes, observe the temperature change in the furnace, and stop evacuating after the alloy is left to stand until the temperature in the smelting furnace is lower than 100°C, and complete the smelting of the alloy; Step 5, coarse crushing: open the furnace cover, collect the ash on the furnace wall, and obtain the ash product; disassemble the crucible connection of the reactor, separate the obtained alloy cake from the slag, manually finish and use a grinder to remove the slag and defects on the surface of the alloy cake, and coarsely crush it into blocks of 50 to 100 mm to complete the coarse crushing; Step 6: Sandblasting: Place the roughly crushed block into a shot blasting machine for 5 to 10 minutes to remove the oxide film on the surface of the block alloy. Use quartz sand with a particle size of 0.5 to 1 mm and a sandblasting pressure of 0.5 to 0.8 MPa to complete the sandblasting. Step 7: Crushing, refining, screening, testing and packaging: Put the shot peened blocks into the crusher for crushing and screening to 0.25-6.30 mm or select the required sieve size according to user needs, take samples of the sieved alloy for chemical composition analysis, and package and store after qualified analysis to complete the preparation of the alloy; The grades of the V-Al alloy include: AlV55-AlV85.

2. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 1, characterized in that: The AlV55 alloy has a weight of Al powder that is 0.868 to 1.055 times that of V2O5 powder, and a weight of Al2O3 coolant that is 0.21 to 0.61 times that of V2O5 powder.

3. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 1, characterized in that: The AlV65 alloy has a weight of Al powder that is 0.735 to 0.867 times that of V2O5 powder, and a weight of Al2O3 coolant that is 0.20 to 0.59 times that of V2O5 powder.

4. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 1, characterized in that: The AlV75 alloy has a weight of Al powder that is 0.635 to 0.734 times that of V2O5 powder, and a weight of Al2O3 coolant that is 0.19 to 0.58 times that of V2O5 powder.

5. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 1, characterized in that: The AlV85 alloy has a weight of Al powder that is 0.557 to 0.634 times that of V2O5 powder, and a weight of Al2O3 coolant that is 0.16 to 0.55 times that of V2O5 powder.

6. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 1, characterized in that: The purity of the V2O5 powder is not less than 99.0%, and Fe≤0.01%, Si≤0.03%, C≤0.01%, N≤0.1%, and the particle size is greater than 325 mesh≤0.045mm.

7. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 1, characterized in that: The purity of the Al powder is not less than 99.9%, Fe≤0.015%, O≤0.071%, C≤0.02%, N≤0.01%, and the particle size is ≤0.075mm through 200 mesh.

8. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 1, characterized in that: The Al2O3 coolant uses Al2O3 powder or returned slag with a particle size of 1-3 mm. The purity of the Al2O3 powder is required to be not less than 99.0%, wherein Fe≤0.05%, Si≤0.02%, N≤0.02%, and C≤0.01%.

9. The method for preparing a high-purity vanadium aluminum alloy with low nitrogen content and low impurities according to claim 8, characterized in that: The purity of the Al2O3 returned slag is not less than 99.0%, and the impurity elements contained therein are Fe≤0.05%, Si≤0.03%, N≤0.08%, and C≤0.05%.

Citation Information

Patent Citations

  • Vanadium-aluminum alloy and preparation method thereof

    CN113957274A

  • Preparation method of high-density vanadium-aluminum alloy

    CN117144170A

  • Method for controlling oxygen and nitrogen of vanadium-aluminum alloy

    CN117604256A

  • Production method of low-iron vanadium-aluminum alloy and vanadium-aluminum alloy

    CN117604354A

Cited By

  • Method for producing vanadium-aluminum alloy by taking smelting vanadium slag as reducing agent

    CN121380567A